Property Analysis of Composable Web services - Wei Liu; Lu Wang; Yuyue Du; Pin Wang; Chun Yan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Web services are basic components constructing a flexible business process software. By composing multiple Web services, a complicated business process across organization and departments can be formed. This paper present a formal model of composable Web services: composed service process nets (CSPNs). Properties of Composable Web services are analyzed based on CSPNs. The relation between a CSPN and its corresponding Web service process subnets are discussed. The property analysis methods of CSPNs are come up with. A dynamic property of CSPNs can be determined based on static net structures by means of the proposed methods.